How is the Wine Consumers Behavior Changing After Pandemic: A Descriptive Analysis of the Chinese Wine Market - Zhang, Ruixin; Gardiner, Paul (Archives of Business Research, 2024)
The COVID-19 pandemic had a substantial impact on the global wine industry, leading to dramatic changes in consumer behavior as well. Although the pandemic has significantly impeded the global economy, international trade, and social development, it has given an impetus to the process of digitalization, digital market has been growing prosperity, especially in China, a country as the bellwether in digitalization. The China wine market is one of the most potential markets in the world, Per capita expenditure of wine in China has increased quite significantly after 2021, compared to the Asia Pacific and global levels. Therefore, understanding how the changes in the Chinese wine consumer occurred after the pandemic will help wineries better enter the Chinese market and develop a digital marketing strategy. After the United Nations proposed the 17 Sustainable Development Goals in 2015, sustainability has become a primary theme of the world’s concern. Therefore, the wine industry has also regarded sustainability as its primary goal. Digital transformation is an inevitable trend that foreign wineries have to face, which is also in conformity with the SDG targets. This paper aims to provide an in-depth understanding of the wine consumer behaviors’ existing circumstances after the pandemic through an exhaustive descriptive analysis, which helps foreign wineries lay down a new business strategy and realize digital transformation in the Chinese wine market.